IMPROVING STUDENTS VOCABULARY MASTERY THROUGH GUESS MY MOVE GAME GENDER-BASED - Arsyi Rizqia Amalia; Suci Afrialy Rusmawan (XXXXXXXX, 2023)
Abstract: English ability of students in SDI Al-Azhar 7 is very closely related to the vocabulary mastery they have that were very low.  In their activity, low grade male students tend to be more active rather than female students, that is why learning process that can engage students activeness is needed to be implemented such as games. Hudges (2010: 225) explains that there is a very strong relationship between language and games especially in the growth and development of students. The purposes of this study are to describe the implementation of GMG model in learning English and to describe the students individual and group English vocabulary mastery by using GMG model. The research method used in this study is Classroom Action Research with Kemmis and Mc. Taggart design. The result of this research shows that GMG learning model can improve students’ English vocabulary mastery both in individual and group scores. Based on the performance of groups divided by gender, group scores indicate that female group get the highest score, but the highest average score is achieved by the male groups. This shows that the activeness of students inside and outside the classroom does not guarantee to the student learning outcomes.Keywords: vocabulary, GMG model, gender